tomoseqr: A Bioconductor package for spatial reconstruction and visualization of 3D gene expression patterns based on RNA tomography - Ryosuke Matsuzawa; Daichi Kawahara; Makoto Kashima; Hiromi Hirata; Haruka Ozaki (PLoS ONE, 2025)
RNA tomography computationally reconstructs 3D spatial gene expression patterns genome-widely from 1D tomo-seq data, generated by RNA sequencing of cryosection samples along three orthogonal axes. We developed tomoseqr, an R package designed for RNA tomography analysis of tomo-seq data, to reconstruct and visualize 3D gene expression patterns through user-friendly graphical interfaces. We show the effectiveness of tomoseqr using simulated and real tomo-seq data, validating its utility for researchers. R package tomoseqr is available on Bioconductor (https://doi.org/doi:10.18129/B9.bioc.tomoseqr) and GitHub (https://github.com/bioinfo-tsukuba/tomoseqr).